Examen especial al rubro activo disponible, cuentas y documentos por cobrar, y ventas de la “Asociación de Trabajadores Acuícolas Cayancas Asotracay” del cantón Huaquillas. Periodo 2021. - Robalino Lituma, Guisella Lizzeth (2023)
The present Curricular Integration Project has been developed to accomplish the proposed objectives, such as: evaluating the internal control system in order to determine compliance with the company's objectives; determining the reasonableness of the information reflected in the Financial Statements of Available Assets, Accounts and Notes Receivable, and Sales; verifying conformity with legal and regulatory provisions applied in the association, and preparing the special examination report, which includes comments, conclusions, and recommendations that serve as a guide to the association's executives in taking timely corrective measures. The methodology used was based on the special examination process. In the first phase, a preliminary and specific planning report was prepared. In the second phase, execution, audit programs, questionnaires, and the evaluation of internal control were carried out to determine their level of risk and reliability. In the third phase, communication of results, a report was drafted which identified the deficiencies found in each of the examined items. After conducting the Special Examination process, it was determined that in the association, the cash component has a risk and reliability level of 85%; savings and credit cooperatives have an 88%; banks and other financial institutions have an 80%; investments in the private and public financial sector have an 87%; accounts and notes receivable have an 88%; and finally, sales have a 79%. It should be noted that the items of available assets, accounts and notes receivable, and sales of the association present reasonable balances. However, there are irregularities such as: personnel not being bonded, lack of training programs, absence of segregation of duties, reconciliations not being properly authorized, and the absence of policies regarding accounts receivable and sales in terms of the application and compliance with certain principles established in COSO.